2015
DOI: 10.1186/s40164-015-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor-dependent and -independent pathways of systemic coagulation activation in acute myeloid leukemia: a single-center cohort study

Abstract: BackgroundIn acute myeloid leukemia (AML), disseminated intravascular coagulation (DIC) contributes to morbidity and mortality, but the underlying pathomechanisms remain incompletely understood.MethodsWe conducted a prospective study on 69 patients with newly diagnosed AML to further define the correlates of systemic coagulation activation in this hematological malignancy. Tissue factor procoagulant activity (TF PCA) of isolated peripheral blood mononuclear cells (PBMCs) and TF expression by circulating microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 53 publications
(46 reference statements)
2
28
0
2
Order By: Relevance
“…97 Plasma DNA and nucleosomes were also associated with an increased risk of mortality within 150 days, suggesting the use of ceDNA as prognostic marker in DIC patients. 97 DNA concentration in cancer patients with DIC was increased compared with healthy controls 98 and DNA levels correlated with plasma levels of D-dimer, thus supporting an association of ceDNA and coagulation in DIC. 98 An independent study showed that levels of nucleosomes in plasma positively correlated with factor XII (FXII) and were significant predictor of mortality in DIC patients.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 69%
See 1 more Smart Citation
“…97 Plasma DNA and nucleosomes were also associated with an increased risk of mortality within 150 days, suggesting the use of ceDNA as prognostic marker in DIC patients. 97 DNA concentration in cancer patients with DIC was increased compared with healthy controls 98 and DNA levels correlated with plasma levels of D-dimer, thus supporting an association of ceDNA and coagulation in DIC. 98 An independent study showed that levels of nucleosomes in plasma positively correlated with factor XII (FXII) and were significant predictor of mortality in DIC patients.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 69%
“…97 DNA concentration in cancer patients with DIC was increased compared with healthy controls 98 and DNA levels correlated with plasma levels of D-dimer, thus supporting an association of ceDNA and coagulation in DIC. 98 An independent study showed that levels of nucleosomes in plasma positively correlated with factor XII (FXII) and were significant predictor of mortality in DIC patients. 99 In summary, these data suggest an association between ceDNA and coagulation, thus identifying ceDNA as a prognostic marker for mortality in DIC.…”
Section: Disseminated Intravascular Coagulationmentioning
confidence: 69%
“…Secondly, caner and blood hypercoagulability correlates with each other. Inflammatory reaction, vascular endothelial injury, coagulation initiation, platelet activation, tumor cell adhesion and aggregation are involved in this process, with a numerous number of cytokines and proteins (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Take platelet activation for example, though it has been demonstrated to correlate with tumor metastasis (38)(39)(40), it is rare to detect the plate activation relevant cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…We chose these indices based mainly on the considerations of representativeness, feasibility, and practicality. In the process of malignant tumor progression or treatment, many biochemical indices can be used to assess coagulation status, such as clotting factors, platelet activation related factors, inflammatory mediators, coagulant substances produced by tumors, tissue factor, and anticoagulant related proteins (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Choosing appropriate indices for evaluating VTE is of clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…In people, several studies have reported that MP-associated TF (MP-TF) activity is associated with increased risk of thrombosis and DIC [3,4,10,19]. On the contrary, there have been few studies of MP-TF activity in dogs with a spontaneous disease.…”
mentioning
confidence: 99%